2004
DOI: 10.1007/s11661-004-0364-5
|View full text |Cite
|
Sign up to set email alerts
|

Damage repair in CMSX-4 alloy without fatigue life reduction penalty

Abstract: The microstructural changes in a single-crystal Ni-base superalloy, CMSX-4, that might occur during the processes of repair and recoating of hot section components for advanced gas turbines were studied. It is shown that the cellular ␥/␥Ј microstructure is formed when the material is subjected to local plastic straining, followed by the reheat treatments during the course of damage recovery. The formation of cellular microstructure in the material led to the remarkably reduced fatigue strength. In order to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
1
20
2
Order By: Relevance
“…The reason why the latter two alloys were selected is from the following reasons: whereas it is possible to get these MCrAlY alloys on commercial base, they are containing boron in significant amount in their chemical compositions (see Table 2). An addition of boron; one of the grain boundary strengthening elements, is expected to have a specific role to minimize the undesirable effects of the cellular microstructure formed in the superalloy substrate (18) (20) . The cellular microstructure might be originated in some cases in new generation Ni-base superalloys during a grit blasting process; an important process to fabricate the TBCs, but it may reduce the high temperature strength of superalloy substrates (18) .…”
Section: Tbc Specimen Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why the latter two alloys were selected is from the following reasons: whereas it is possible to get these MCrAlY alloys on commercial base, they are containing boron in significant amount in their chemical compositions (see Table 2). An addition of boron; one of the grain boundary strengthening elements, is expected to have a specific role to minimize the undesirable effects of the cellular microstructure formed in the superalloy substrate (18) (20) . The cellular microstructure might be originated in some cases in new generation Ni-base superalloys during a grit blasting process; an important process to fabricate the TBCs, but it may reduce the high temperature strength of superalloy substrates (18) .…”
Section: Tbc Specimen Preparationmentioning
confidence: 99%
“…Many types of precipitates are appearing, depending on the alloy systems. These precipitates were identified by CoAl in the CoNiCrAlY, CoAl and borides in the CoNiCrAlY+B, and Ni 3 Al and NiAl with a little borides in the HaynesC22 (20) . Induction heating system (2) Mechanical and Physical properties Mechanical properties of the virgin and aged bond coat alloys were measured by means of the self-standing MCrAlY alloy specimens, where the aging was conducted at 1000℃ for 1000 hours in air.…”
Section: Basic Properties Of Mcraly Bond Coat Alloys (1) Microstructuresmentioning
confidence: 99%
“…There is another important report which revealed that surface re-crystallization formed during service at elevated temperatures was promoted by the residual stress that had been applied to the components during machining. 9) It is thus easily anticipated that surface crystal orientation, and/or pre-surface treatments prior to coating can affect the SRZ formation kinetics. However, to the best of our knowledge, there are very few reports investigating such effects, except for the authors' group.…”
Section: Introductionmentioning
confidence: 99%
“…The directions of gas turbine development are not only to achieve high thermal efficiency but also cost reduction for production and maintenance [13]. Thus, repair, recoating and refurbishment technologies for the hot section components are important.…”
Section: Introductionmentioning
confidence: 99%